Abl Interactor 1 Binds to Sos and Inhibits Epidermal Growth Factor- and v-Abl-Induced Activation of Extracellular Signal-Regulated Kinases - Fan, Pang-Dian (American Society for Microbiology, 2000)
Recent studies have suggested that members of the Abl interactor (Abi) protein family negatively regulate cell growth and transformation. To date, however, no specific role in these cellular processes has been identified for the Abi family. Here we describe the inhibition by overexpressed Abi-1 of a mitogenic pathway activated by both growth factors and v-Abl. We have identified the guanine nucleotide exchange factors Sos1 and Sos2 as novel binding partners of Abi-1. A domain that is required for interaction with Sos in vivo has been mapped to the amino terminus of Abi-1. Overexpression of Abi-1 inhibits epidermal growth factor (EGF)-induced activation of extracellular signal-regulated kinases (Erks) but does not affect EGF-induced activation of c-Jun N-terminal kinase or Akt. In addition, overexpression of Abi-1 blocks Erk activation induced by v-Abl. In both cases, the maximal inhibitory effect requires an intact amino-terminal Sos-binding domain in Abi-1. Finally, we demonstrate that tyrosine phosphorylation of endogenous Abi-1 in fibroblasts is induced by both v-Abl and serum stimulation, further suggesting a role for Abi-1 in signal transduction initiated by v-Abl and growth factors. Taken together, these findings suggest that overexpressed Abi proteins negatively regulate cell growth and transformation by specifically targeting the Erk pathway.